The Michigan infant mental health home visiting model. Issue 2 (3rd April 2020) - Weatherston, Deborah J.; Ribaudo, Julie; ,
ABSTRACT: Selma Fraiberg's pioneering work with infants, toddlers, and families over 40 years ago led to the development of a field in which professionals from multiple disciplines learned to work with or on behalf of infants, very young children, their parents, and the relationships that bind them together. The intent was to promote social and emotional health through enhancing the security of early developing parent–child relationships in the first years of life (Fraiberg, 2018). Called infant mental health (IMH), practitioners from fields of health, education, social work, psychology, human development, nursing, pediatrics, and psychiatry specialize in supporting the optimal development of infants and the developing relationship between infants and their caregivers. When a baby is born into optimal circumstances, to parents free of undue economic and psychological stressors and who are emotionally ready to provide care and nurturing for an infant's needs, an IMH approach may be offered as promotion or prevention, with the goal of supporting new parent(s) in developing confidence in their capacity to understand and meet the needs of the tiny human they are coming to know and care for. However, when parental history is fraught with abandonment, loss, abuse or neglect, or the current environment is replete with economic insecurity, threats to survival due to interpersonal or community violence, social isolation, mental illness, or substance abuse, the work of the IMH therapist may require intervention or intensive treatment and becomes more psychotherapeutic in nature. The underlying therapeutic goal is to create a context in which the baby develops within the environment of a parent's nurturing care without the psychological impingement that parental history of trauma or loss or current stressors such as isolation, poverty, or the birth of a child with special needs, can incur.